Enhancing Awareness of the Sleep’s Importance among Students: A Qualitative Study - Mareike Seska Diana Lotulung; Juwinner Dedy Kasingku (Universitas Muhammadiyah Enrekang, 2024)
Sleep is a vital biological state for humans, crucial for the body's recovery and enhancement of human stamina. In its complex process, sleep plays a crucial role in maintaining daily functions. Lack of sleep can result in concentration disturbances, decreased endurance, fatigue, anxiety, and decreased thinking ability, to other health issues. Particularly for students, insufficient sleep can have a negative impact on their academic performance. This study is a qualitative research with a literature review approach, comparing various existing research results. Sleep is extremely important for humans, including students. Therefore, the importance of adequate sleep time for students to support optimal academic achievement is significant.